Handelssanktionen – Wirkungen und Nebenwirkungen; Trade Sanctions: Effects and side effects - Thieß Petersen; Thomas Schwab (Wirtschaftsdienst, 2022)
Länder setzen immer wieder Wirtschaftssanktionen gegen andere Nationen ein, um diese zu einem bestimmten Handeln zu bewegen. Ein verändertes Verhalten soll dadurch erwirkt werden, dass dem von der Sanktion betroffenen Land ein wirtschaftlicher Schaden zugefügt wird. Er erhöht den Preis für Handlungen, die als unerwünscht angesehen werden. Dieser Beitrag untersucht die ökonomischen Auswirkungen von Handelssanktionen auf die beteiligten Volkswirtschaften und diskutiert diese in der aktuellen Situation mit Russland. – – Trade sanctions have been repeatedly used as an instrument to force countries to change policies or actions that are considered condemnable. Trade sanctions put pressure on a country by purposefully harming its economy. The resulting economic costs are intended to translate into political costs for the government of the target country. In this article, we outline the economic mechanisms behind trade sanctions and resulting effects for both the implementer and the target country. We also discuss the implications of our findings in light of the current sanction regime against Russia.
Keywords: F51; F52; F43; 330